2006
DOI: 10.1002/joc.1455
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the dehydration‐greenhouse feedback over the Arctic during February 1990

Abstract: Abstract:The effect of pollution-derived sulfuric acid aerosols on the aerosol-cloud-radiation interactions is investigated over the Arctic for February 1990. Observations suggest that acidic aerosols can decrease the heterogeneous nucleation rate of ice crystals and lower the homogeneous freezing temperature of haze droplets. On the basis of these observations, we hypothesize that the cloud thermodynamic phase is modified in polluted air mass (Arctic haze). Cloud ice number concentration is reduced, thus prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Using a refined treatment of the IN de‐activation effect based on laboratory experiment, this research has confirmed the results obtained in previous modeling investigations (Girard et al , 2005; Girard and Stefanof, 2007) on the effect of acid coating on the Arctic clouds and radiative budget during winter. This indirect effect of acid aerosols on arctic clouds and the resulting atmospheric cooling could explain, at least in part, the unexpected observed cooling trend of surface air temperature over the Arctic Ocean during winter in the period 1979–1999 as observed by boys (Rigor et al , 2000) and by satellite remote sensing (Wang and Key, 2003).…”
Section: Summary and Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Using a refined treatment of the IN de‐activation effect based on laboratory experiment, this research has confirmed the results obtained in previous modeling investigations (Girard et al , 2005; Girard and Stefanof, 2007) on the effect of acid coating on the Arctic clouds and radiative budget during winter. This indirect effect of acid aerosols on arctic clouds and the resulting atmospheric cooling could explain, at least in part, the unexpected observed cooling trend of surface air temperature over the Arctic Ocean during winter in the period 1979–1999 as observed by boys (Rigor et al , 2000) and by satellite remote sensing (Wang and Key, 2003).…”
Section: Summary and Discussionsupporting
confidence: 84%
“…The acid aerosol scenario shows a tropospheric cooling ranging between 0 and 2 K when compared to an uncoated aerosol scenario. Girard and Stefanof (2007) have used a regional climate model with prognostic aerosols to evaluate the effect of acid aerosols on the Arctic surface radiative budget for February 1990. They have assumed two aerosol scenarios: (1) an acid scenario in which the reduction of the IN concentration depends on the sulphate concentration and (2) a natural aerosol scenario in which the IN concentration is unaltered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field measurements show that Arctic haze aerosol had lower ice nucleus (IN)‐to‐particle ratios and slower ice nucleation rates than aerosol in unpolluted troposphere, which is hypothesized to be caused by sulfuric acid coating on existing IN in Arctic haze [ Borys , ]. Several large‐scale modeling studies have been conducted on potential effects of acid‐coated IN in clouds; these include a reduced ice number promoting further ice crystal growth and precipitation [ Girard and Stefanof , ], a less frequent glaciation of mixed‐phase clouds leading to longer cloud lifetimes and higher cloud albedos [ Hoose et al ., ; Storelvmo et al ., ; Du et al ., ], and an increased occurrence of Arctic mixed‐phase clouds leading to more atmospheric cooling in winter [ Girard et al ., ]. Arctic clouds and their radiative forcing in climate models are sensitive to parameterizations of IN, especially in winter [ Du et al ., ; Xie et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the SIFI effect can also not be tested directly from the satellite measurements alone, because we can hardly design a credible proxy for in‐cloud sulphate concentrations. Hence, in this paper, we test the SIFI potential consequence according to which higher sulphate concentrations favor cloud populations made of larger ice crystals, caused by a reduction in the competition for water vapor when fewer IFN may operate [ Girard and Stefanof , 2007]. To achieve this task we have developed the Arctic Winter Aerosol and Cloud Classification from CloudSat and CALIPSO (AWAC4) algorithm.…”
Section: Introductionmentioning
confidence: 99%